Analisis Pengaruh Dana Desa Terhadap Pengentasan Kemiskinan Di Sumatera Utara - Winda Lestari Gurning (TANSIQ: Jurnal Manajemen Dan Bisnis Islam, 2020)
The purpose of this study was to analyze the influence of the Village Program Fund on poverty alleviation in North Sumatra. The study population was villages in North Sumatra province that received the Village Fund Program, namely the districts of South Nias, Simalungun, Deli Serdang, Padang Lawas and Mandailing Natal. The analysis tool uses twin regression with panel data for hypothesis testing with the F test, t test, and the coefficient of determination (????2) at the error rate ???? = 5%. From the simple regression program analysis above shows the calculated F value of 1.660 with a significance value of 0.288 If the significance value of F arithmetic <0.05 then the alternative hypothesis is accepted, so that the Village Fund Budget variable influences poverty. The regression results show that the R-Square value is 0.356 or 35.5%. This means that the Village Fund Budget reduces poverty by 25.5% while the remaining 64.5% is contributed by other variables not examined in this study.